Characterizing Thermal Populations in a Coupled Superconducting Aluminum 3Dcavity and a Transmon Qubit - Hagström, Ivan (My University, 2023)
Circuit quantum electrodynamics (cQED), which combines superconducting qubits with microwave resonators, has become one of the leading platforms for quantum computation [1]. Continuous variable quantum computation (CVQC), which uses the bosonic modes of a quantum microwave resonator as a quantum memory, has some advantages over discrete quantum computing, including long lifetimes and simple schemes for error correction [2]. The presence of thermal excitations in a continuous variable system can increase error rates and reduce the fidelity of quantum operations. This provides the motivation to characterize the residual thermal population of our systems. In this thesis we demonstrate methods for characterizing the residual thermal populations in a coupled superconducting 3D-cavity and transmon qubit. First, the qubit population was measured following the scheme from Geerlings et al. (2013) [3]. The measured population was 0.25 ± 0.06% corresponding to an effective temperature of 50.2 ± 1.9 mK. Second, two different methods were used to measure the thermal population of the 3D-cavity. One based on Rabi driving and one based on Ramsey interferometry. Of the two, the method using Rabi driving seemed to perform better at small populations in terms of standard deviation. With this method we measuring a residual population of 0.34 ± 0.03% corresponding to an effective temperature of 37.6 ± 0.3 mK. Finally, the thermal population of an on-chip readout resonator coupled to the qubit was estimated using the photon induced dephasing of the qubit. This gave a population of < 0.18% corresponding to an effective temperature of < 56.1 mK. These results compare favorable to previous studies such as J. M. Gertler et al. (2021) who measured a cavity population of 1-2% and a transmon population of 5% in a similar system [4], and R. W. Heeres et al. (2017) who measured a population of 2% in their cavity and 5% in their transmon [5]. An additional sub-goal of this thesis was measuring the quality factor of a niobium 3D-cavity. Using a circle fit [6], a quality factor of approximately 4.3 million was measured, which is an expected result for an unpolished cavity.
Keywords: 3D-cavity; Circuit quantum electrodynamics; Continuous variable quantum computing; qubit; thermal excitation; thermal population